Analysis of osseointegration of implants with macrogeometries with healing chambers: a randomized clinical trial - Patrícia Tolentino da Rosa de Souza; Rafael Manfro; Fernando Anunziato Ogg de Salles Santos; Gislaine Fernandes Felipe Garcia; Nayara Flores Macedo; Bruno Eduardo Sant’Anna Falce de Macedo; Sérgio Aparecido Ignácio; Edvaldo Antônio Ribeiro Rosa; Evelise Machado de Souza; Luciana Reis Azevedo-Alanis (BMC Oral Health, 2024)
Abstract Background To verify the influence of macrogeometry with healing chambers on the osseointegration of dental implants by analyzing implant stability quotient (ISQ) and evaluate the correlation between insertion torque and ISQ insertion with different macrogeometries. Methods In total, 26 implants were installed in the posterior mandible of eight patients with sufficient bone height for the installation of implants measuring 3.5 mm in diameter and 9.0 mm in length. The implants were categorized according to two types of macrogeometry: a test group (GT) with 13 conical implants with healing chambers and a control group (GC) with 13 conical implants with conventional threads. To insert the implants, a bone drilling protocol was used up to a diameter of 3 mm with the last helical bur. The insertion torque of the implants was evaluated, followed by the measurement of ISQ at 0 (T-0), 7 (T-7), 14 (T-14), 21 (T-21), 28 (T-28), and 42 (T-42) days. Results The mean insertion torque was 43 Ncm in both groups, without a significant difference. Moreover, no significant difference in the ISQ values was found between the groups at different time points (p > 0.05), except at T-7 (GT = 69.87±1.89 and GC = 66.48±4.49; p = 0.01). Although there was no significant difference, ISQ median values were higher in the GT group than GC group at 28 days (GT = 67.98 and GC = 63.46; p = 0.05) and 42 days (GT = 66.12 and GC = 60.33; p = 0.09). No correlation was found between the insertion torque and ISQ insertion (p > 0.05). Conclusion Furthermore, implants with a 3.5 mm diameter macrogeometry, with or without healing chambers, inserted with a drilling protocol up to 3 mm in diameter of the last helical bur, led to a similar secondary stability, with no difference in ISQ values. Although, implants with healing chamber demonstrates ascending values in the graph of ISQ, having a trend of faster osseointegration than implants without healing chambers. Both macrogeometries provide a similar primary stability to implants. Trial registration This study was registered retrospectively in ReBec (brazilian registry of clinical trials) under the number RBR-96n5×69, on the date of 19/06/2023.